UJI COBA PEMBELAJARAN KIMIA FISIKA III BERBANTUAN INTERNET - Bertha Yonata, ; Suyono, (Jurnal Penelitian Pendidikan Matematika dan Sains, 2008)
The purposes of this research are to find out the feasibility of implementation internet assisted learning and chemistry students learning outcomes after attended learning assisted by internet. The research has been implemented to 12 chemistry students of Kimia Reguler 2005 FMIPA Unesa class at odd semester 2007-2008. This research is a descriptive research that describe about learning feasibility, students learning outcomes, and student respons about learning set and teaching-learning process. The result of this research show that RPP feasibility is good (3,33 - 4,00). Students learning outcomes show 100,00% of the students reach point more than 66. Students satisfied with learning assisted by internet. The conclusions of this research are learning assisted by internet of Reaction Rate and Factors Affect Reaction Rate topic has carried out, studentss response positive, and  students have completely master the learning.